2016
DOI: 10.1120/jacmp.v17i5.6252
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of identical VMAT plans with and without jaw tracking technique

Abstract: The unwanted radiation transmission through the multileaf collimators could be reduced by the jaw tracking technique which is commercially available on Varian TrueBeam accelerators. On the basis of identical plans, this study aims to investigate the dosimetric impact of jaw tracking on the volumetric‐modulated arc therapy (VMAT) plans. Using Eclipse treatment planning system (TPS), 40 jaw‐tracking VMAT plans with various tumor volumes and shapes were optimized. Fixed jaw plans were created by editing the jaw c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
4
19
0
Order By: Relevance
“…While agreeing with aforementioned retrospective reports, our clinically optimized synchronous JT‐VMAT plan exhibits superior OAR protection for normal lung doses as well as other OAR sparing prospectively compared to no JT‐VMAT for the given complexity of single‐isocenter/two‐lesion lung SBRT setting. By tracking the jaws during SBRT VMAT plan optimization, the magnitude of normal lung dose reductions (the OAR closest to the multiple targets) observed in this study were generally consistent with previous studies, yet relatively higher differences (up to 11%) were observed, perhaps due to the unique complexity of the clinical situations and the distance between the tumors. It is worthwhile to mention that MLC transmission of our 6 MV‐FFF beam was 1.2% and was modeled by the TPS and incorporated in the dose calculation.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…While agreeing with aforementioned retrospective reports, our clinically optimized synchronous JT‐VMAT plan exhibits superior OAR protection for normal lung doses as well as other OAR sparing prospectively compared to no JT‐VMAT for the given complexity of single‐isocenter/two‐lesion lung SBRT setting. By tracking the jaws during SBRT VMAT plan optimization, the magnitude of normal lung dose reductions (the OAR closest to the multiple targets) observed in this study were generally consistent with previous studies, yet relatively higher differences (up to 11%) were observed, perhaps due to the unique complexity of the clinical situations and the distance between the tumors. It is worthwhile to mention that MLC transmission of our 6 MV‐FFF beam was 1.2% and was modeled by the TPS and incorporated in the dose calculation.…”
Section: Discussionsupporting
confidence: 89%
“…A few investigators have reported the dosimetric advantages of jaw tracking techniques for IMRT and VMAT planning . For instance, Joy et al . has shown the overall reduction of normal tissues V5, V10, and V20 doses by about 2% when applying jaw tracking for the step‐and‐shoot IMRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even for jaw‐tracking technique, the planner‐defined values still determine the largest field size within which MLCs can modulate the beams. Tracking jaws are only programmed to reduce the low dose spillage outside MLC apertures, but are not optimized for finding the best MLC sequences 3. Limited by the physical constraints of MLCs such as translational range and speed, large jaw settings may impede the MLCs to reach the best location timely to shield the OAR,4 while small jaw size may induce inadequate target dose coverage.…”
Section: Introductionmentioning
confidence: 99%